Instructors' perceptions of the effect of breadth and depth of lexical knowledge on english-major undergraduates' speaking skill - Harem Qasim Saleem; Abdul-Nafi Khidhir Hasan (QALAAI ZANIST JOURNAL, 2020)
This study investigates the instructors' viewpoints on the effect of breadth and depth of lexical knowledge on English-major undergraduates' speaking skill. To achieve the objectives of this research, data were collected through a questionnaire which consists of 21 items and each item has 5 options. It was filled in by twenty instructors from the College of Basic Education, College of Education and College of Language at Salahaddin University-Erbil. The results of the questionnaire showed that, in general the EFL instructors believed that the quality of EFL learners' speaking skill and speaking proficiency to an extent depend on the quantity an depth of vocabulary knowledge.